(untitled) (IAHS Medical Journal, 2026)
Background: The emergence of the blaNDM-1 gene, a potent metallo- b-lactamase conferring resistance to carbapenems, has become a major global public health concern, particularly among multidrug-resistant Pseudomonas aeruginosa strains, which complicates treatment options and exacerbates the burden of antimicrobial resistance. This research is performed to determine the prevalence of the blaNDM-1 gene in Pseudomonas spp.and the phylogenetic diversity pattern of the blaNDM-1 gene. Materials and methods: This cross-sectional study was conducted in the Department of Microbiology, Chittagong Medical College where Pseudomonas spp. was identified conventionally and the antimicrobial susceptibility pattern was performed by modified Kirby Bauer disc diffusion method. Carbapenemase-producing Pseudomonas spp. was determined by phenotypically (mCIM) and molecular tests (PCR). Sequencing of the blaNDM-1 gene was done by automated Sanger sequencing. Results: From urine, wound swab, endotracheal aspirate, sputum and blood Pseudomonas spp. (21.86%) was identified phenotypically. Antimicrobial susceptibility tests revealed resistance to Imipenem (24.53%) and Meropenem (30.19%) with a total of carbapenem resistance (33.33%). Carbapenemase producers were determined by mCIM (24.07%) and the detected blaNDM-1 gene (37.04%). Nucleotide sequencing of randomly selected blaNDM-1 gene was done and a phylogenetic tree was constructed. Conclusion: This study shows the existence of silent AMR genes with an association between phenotypic and molecular methods. To combat the limitation of phenotypic tests, molecular methods may be a good alternative to detect resistance cases to overcome treatment failure where facilities are available IAHS Medical Journal Vol 8(1), June 2025; 52-59